Study of Cocoa Powder Production Process and Packaging Technology in UGM Cocoa Teaching and Learning Industry - Nabila, Salsa Olivia; Wijayanti, Nur (Indonesian Journal of Food Technology, 2024)
UGM Cocoa Teaching & Learning Industry (UGM CTLI) is a business unit based on cocoa processing as a learning and industrial pioneer and provides makloon services to produce cocoa products according to SNI standards. One of the processed cocoa products that has the highest product demand is cocoa powder because it has large market potential as a raw material for the food and beverage industry. The quality of cocoa powder can decrease during the processing process, storage process and distribution process, so it is necessary to study the production and packaging processes regarding their function in maintaining product quality from damage. This research was carried out on January 2 - January 31 2024. Data collection methods used included interviews, observation, documentation and literature study. The cocoa powder packaging used is in the form of a sewing bag consisting of kraft paper and HDPE plastic. Based on the results of previous research, the use of HDPE plastic is considered appropriate and able to protect the quality of cocoa powder better than other plastics.